Evaluation of The Implementation of Siakad 4.0 at Stai Darul Falah: Analysis of Student Satisfaction, Administrative Obstacles, and Academic Service Efficiency - Fauzi, Helmi Al Hafid; Nugraha, Mulyawan Safwandy; Ibnu Imam Al Ayyubi; Eko Prayetno; Syed Muhammad Adib Termizi b, Ahmad al-Jafari (Mudir: Jurnal Manajemen Pendidikan, 2025)
As an Islamic religious higher education institution, STAI Darul Falah has additional challenges in ensuring that the application of technology remains in line with Islamic values. This is a major concern, considering that the technology used must support the institution's mission of producing graduates who are not only intellectually intelligent but also have high moral and spiritual integrity. This research aims to evaluate the effectiveness of SIAKAD 4.0 at STAI Darul Falah using quantitative and qualitative approaches. This research uses a mixed-method approach, which combines quantitative and qualitative methods to gain a comprehensive understanding of the effectiveness of SIAKAD 4.0 at STAI Darul Falah. The population in this study includes all students and academic management staff who actively use SIAKAD 4.0 at STAI Darul Falah with a sample consisting of 100 students and 10 academic management staff. This research shows that the implementation of SIAKAD 4.0 at STAI Darul Falah has had a significant positive impact on the efficiency and quality of educational services. This system has succeeded in increasing the speed of administrative services, reducing error rates, and increasing the accessibility of academic data for students and administrators. The results of the questionnaire analysis indicate that the majority of students are satisfied with the convenience and benefits offered by this system. However, several aspects still require improvement. However, this research also revealed several obstacles faced in implementation, including limited technological infrastructure and a lack of technical training for managers.